Environmental design studies on perception and simulation: an urban design approach - Barbara Piga; Eugenio Morello (Ambiances)
Perceptual simulation represents an attempt to anticipate physical reality, whereby people can experience and interpret future environments from a subjective perspective. Working on experiential simulation for urban and landscape design requires an understanding of the relationship between man and the environment from a perceptual and cognitive standpoint. In fact, only by investigating the sensing and cognitive processes behind perception can we establish an informed approach to simulation of places and their ambiances. In particular, we propose a parallelism between man/environment and man/simulation relationships, aiming at giving back a framework for replicating in simulation the multisensory aspects that occur in the perception of the physical world. Hence, the objective of this article is to present how we approach the dimension of perceptual simulation within our research and professional work as urban designers. From a methodological point of view, we explored the topic through two main tasks, namely the selection and reconstruction of the research context and the key issues of perceptual simulation finalized in the second task, i.e. the construction of a set of simulation tools for urban design, intended as a matrix of possible practical applications. In particular, the theoretical framework presented in this work consists of a selection and overview of references relevant to urban design, comprehension of the research context and delivery of the set of tools implemented within our research unit. This matrix of tools represents the novelty of this work and is intended as a practical reference for orienting the choice among different simulation tools within the urban design practice. For instance, it is important to highlight the efficacy of each type of simulation in mimicking the man/environment relationship.